Pemanfaatan Media Wayang Kertas Untuk Meningkatkan Mutu Perkembangan Karakter Bahasa Anak Dalam Berkomunikasi Verbal - Natal Kristiono; Mutmainah (UHN IGB Sugriwa Denpasar, 2018)
Early childhood education itself is education aimed at preschool children with the aim that children can develop their potential from an early age so that they can develop naturally as children. Based on experience in TK Negeri Pembina Belik, Researchers found a problem in the language character of students, namely the lack of verbal communication between students with one another, children are still quiet and rarely communicate directly with their peers. The formulation of the problem to be studied in this study is the lack of communication activities among peers due to the lack of communication support media that attracts and motivates children to start a conversation or communication directly / verbally. The use of paper puppet media carried out in two cycles has a positive impact on several components of activities, especially for students. Children are more actively communicating, independent, fostering self-confidence, and strong curiosity. The application of this media can be carried out in various learning and development aspects.